Implikasi Hukum Pengalihan Hak Atas Tanah Tanpa Keterlibatan Pejabat Pembuat Akta Tanah - Habiba, Habiba; Sisman, Wandhi Pratama Putra (Faculty of Law, Andalas University, 2025)
The transfer of land rights in Indonesia is legally required to be carried out before a Land Deed Official (Land Deed Official or PPAT) in order to obtain legal force and be registered with the Land Office. However, in practice, many land sale and purchase transactions are conducted without the involvement of a PPAT, often relying only on private deeds. This study aims to analyze: The legal implications arising from land transfers without PPAT involvement, and The dispute resolution mechanisms available for such cases. The research employs a normative juridical method with statutory, case, and conceptual approaches, supported by literature review and previous studies. The findings reveal that land sale and purchase agreements made. The implications include risks of double transactions, weak legal protection for bona fide buyers, and potential economic losses. Dispute resolution may be pursued through non-litigation mechanisms (mediation, facilitation by the National Land Agency) or litigation (general courts and administrative courts). This study emphasizes that the involvement of PPAT is not merely an administrative formality but a crucial instrument to ensure legal certainty and protection in land transactions in Indonesia.